The Implementation of Project Based Learning to Enhance Students' Understanding of Environmental Conservation and Disaster Mitigation - Londa, Treesje Katrina; Kamaruddin, Kamaruddin (Universitas Muhammadiyah Makassar, 2023)
The aim of this research is to provide junior high school students with learning experiences to increase their understanding of environmental conservation and disaster mitigation. This study focuses on reforestation and disaster mitigation efforts through the application of project-based learning models in the surrounding environment. This research was a descriptive study with a post-test design approach, conducted at SMPN Ranoyapo, South Minahasa Regency. There were 42 students of class VII who participated in this study. The results of this research showed that the students' understanding of environmental conservation was in the level of excellent category (26%), good category (48%), fairly good category (24%), and poor category (2%). Meanwhile, the highest average percentage of students' understanding of disaster mitigation efforts was in the excellent category (41%), followed by the good category (39%), fairly good category (16%), and poor category (4%). These results indicate that project-based learning can improve students' understanding of learning, particularly that related to environmental learning.